2018
DOI: 10.1002/chem.201800770
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Based Nanozymes: Multienzyme Redox Activity and Effect on the Nitric Oxide Produced by Endothelial Nitric Oxide Synthase

Abstract: Nanomaterials having enzyme-like activity (nanozymes) make them suitable candidates for various biomedical applications. In this study, we demonstrate the morphology-dependent enzyme mimetic activity of Mn O nanoparticles. It is found that Mn O nanoparticles mimic the functions of all three cellular antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Interestingly, the nanozyme activity of Mn O depends on various factors including size, morphology, surface area, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 94 publications
1
68
0
1
Order By: Relevance
“…44,45 MONPs are reported to selectively scavenge superoxide ( • O 2 − ) species but not nitric oxide (NO • ) species. 46 This could have resulted in attenuation of mechanical allodynia without the attenuation of thermal hyperalgesia. We next investigated whether MONPs administration has any efficacy against nociceptive pain though tail flick test and we found no efficacy against nociceptive pain as expected ( Figure S4).…”
Section: Intrathecal Injection Of Monps Attenuates Mechanical Allodynmentioning
confidence: 99%
“…44,45 MONPs are reported to selectively scavenge superoxide ( • O 2 − ) species but not nitric oxide (NO • ) species. 46 This could have resulted in attenuation of mechanical allodynia without the attenuation of thermal hyperalgesia. We next investigated whether MONPs administration has any efficacy against nociceptive pain though tail flick test and we found no efficacy against nociceptive pain as expected ( Figure S4).…”
Section: Intrathecal Injection Of Monps Attenuates Mechanical Allodynmentioning
confidence: 99%
“…The shape and morphology of nanozymes plays a key role in regulating their catalytic activity [49][50][51][52]. Tian et al have investigated the effect of different morphologies (nanosheets, nanofibers, and nanorods) of VO 2 nanoparticles on the colorimetric assay for H 2 O 2 and glucose [53].…”
Section: Morphologymentioning
confidence: 99%
“…Based on the research on the crystal structure of GPx and the investigation of biomimetic GPx, it was indicated that hydrophobic cavity derived from the hydrophobic amino acid residues of 150 Phe, 148 Trp, and 34 Leu played an important role in maintaining the high catalytic activity. 1,2 In this study, the hydrophobic structure of the natural GPx was simulated using the hydrophobic microenvironment derived from the PNIPAM polymer scaffold during the temperature responsive process.…”
Section: Catalytic Mechanism Of Pntegelmentioning
confidence: 99%
“…Generally, the scaffold materials for preparing biomimetic GPx mainly include small organic molecules, 12,13,[20][21][22] imprinted proteins, 8,11 genetically engineered proteins, 14,15,23 supramolecular polymers, 17,19,24,25 block polymers, [26][27][28][29] microgels, [30][31][32] and organic-inorganic hybrid materials. [33][34][35][36] Compared with natural GPx, these biomimetic GPx were endowed with obvious advantages, such as high preparation yield, strong structural stability and good industrialization prospect. Among the scaffold materials of these biomimetic GPx, the microgel scaffold exhibits unique characteristics.…”
Section: Introductionmentioning
confidence: 99%